Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5430/jnep.v7n2p10
|View full text |Cite
|
Sign up to set email alerts
|

Perceived genetic knowledge among pre-licensure undergraduate nursing students

Abstract: Objective: This study assessed the perceived retention of genetic knowledge of pre-licensure undergraduate nursing students who received a stand-alone genetics course. Methods: Design: Two analyses of total score were of interest: 1) Assessment of retention of knowledge of education group at sophomore level [n = 62; 2013], junior level [n = 60; 2014] and senior level [n = 42; in 2015] and 2) Comparison of the education group [n = 62] to a control group who learned genetic content that was woven into their cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(48 reference statements)
0
12
0
1
Order By: Relevance
“…[7,11,33,40] It is required of nursing faculty to prepare students for the emerging genetic-genomic content and its application to practice. This "preparation extends far beyond the science and technology", addressing "the issues that promote patient adaptation to, as well as personal and clinical decisions" and their possible consequences, and the "interpretation and impact of information, risk perception, and available resources".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,11,33,40] It is required of nursing faculty to prepare students for the emerging genetic-genomic content and its application to practice. This "preparation extends far beyond the science and technology", addressing "the issues that promote patient adaptation to, as well as personal and clinical decisions" and their possible consequences, and the "interpretation and impact of information, risk perception, and available resources".…”
Section: Discussionmentioning
confidence: 99%
“…A well-prepared nursing faculty is needed to adequately prepare the future generation of professional nurses. The incorporation of the requisite knowledge, skills and abilities continue to fluctuate in the nursing profession [33] and maintaining educational competency to meet this need is incumbent of nurse educators to adequately teach this content. The number of nurses whose education has prepared them to take over advanced practice roles is currently not sufficient and this deficiency is expected to continue through the next decade.…”
Section: Nurse Educators and Genetic-genomic Knowledgementioning
confidence: 99%
“…[7] Numerous studies have explored pre-licensure selfreported/perceived genomic knowledge and comfort level. [2,[8][9][10][11][12][13] One of the initial analyzes of genomic knowl-edge, the Genetics Literacy Assessment Instrument (GLAI), a 31-item multiple choice test, was utilized to assess undergraduate nonscience majors. [14] It was viewed as a reliable assessment to track acquisition and retention of genomic concepts amongst nursing students and nurse educators and related coursework was found to enhance scores.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[14] It was viewed as a reliable assessment to track acquisition and retention of genomic concepts amongst nursing students and nurse educators and related coursework was found to enhance scores. [2] A study utilizing the GLAI on nursing students revealed that although education perceptibly had an impact on total score, selfreported knowledge retention was lacking, with average total score of one cohort of students at 70% in 2013, 67% in 2014 and 62% in 2015. [2] Another instrument, a 15-item multiple choice survey, initially devised to explore baccalaureate nurse educators' self-perceived genetic knowledge in the United States, was validated to be an effective tool for clarity, accuracy and comprehensiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation